Jumping spiders attend to information from multiple modalities when preparing to jump. (January 2021) - Aguilar-Arguello, Samuel; Taylor, Alex H.; Nelson, Ximena J.
Abstract : Animals often rely on different sources of information when making decisions about the environment. Here, we assessed whether two jumping spiders (Salticidae), Trite planiceps and Portia fimbriata, take two different sources of information into account when jumping over water, to which they are averse. Specifically, we investigated whether salticids can assess both mechanical (wind) and visual cues (distance) while jumping from one platform within a pool arena to another. In the first experiment, salticids were exposed to either no wind, low wind speed or high wind speed. Spiders adjusted the horizontal direction of the jump depending on wind presence, such that the wind would favour the jump. Furthermore, independent of wind presence, the vertical trajectory of the jump affected jump outcome (success or failure) in Portia, but not in Trite . In a second experiment, salticids were exposed to intermittent wind in 10 s bouts to assess whether they preferred to jump during bouts without wind. As expected, spiders preferred to jump when there was no wind. Overall, we found that salticids do account for wind conditions when initiating a potentially risky jump, but that sound also affects salticid behaviour before the jump, possibly due to stress. Highlights: Animals rely on different information sources when making decisions. We gauged jumping spider's ability to attend to vision and wind-based cues in jumps. Spiders used both sources of information to 'calculate' jump trajectories. Wind affected spider's ability to make careful judgements, suggesting trade-offs.